KARAKTERISTIK BIODIESEL DENGAN MENGGUNAKAN ETANOL KONSENTRASI RENDAH - Erlinda Ningsih; Suparto (Journal of Research and Technology, 2017)
Biodiesel is produce by transesterification process using alcohol and the most alcohol used in biodiesel manufacturing is methanol. Methanol is made from non-renewable material. Whereas, ethanol made from renewable materials and the price of pure ethanol is expensive. So, research to produce biodiesel with low ethanol concentration was conducted. This research was aimed to know the mole ratio of oil toward ethanol and the best reaction time in this biodiesel production. The mole ratios of oil toward ethanol used were 1:12, 1:14, 1:16 and the time reactions were one, two, and three hours. This research was started by heating the oil to temperature 60oC, then adding ethanol solution and NaOH and being reacted into several variations of time. After that, the separating and washing process were executed. From the analysis result, the biodiesel produced is appropriate with the requirements of SNI 04-7182-2006.